Exploring critical success factors for stakeholder management in construction projects - Yang, Jing; Shen, Geoffrey Qiping; Ho, Manfong; Drew, Derek S.; Chan, Albert P. C. (Journal of Civil Engineering and Management, 2009)
With a focus on different aspects of stakeholder management, various sets of critical success factors (CSFs) have been suggested in the literature. It is crucial to explore the relative importance and groupings of these factors. This paper aims to identify CSFs associated with stakeholder management in construction projects, and explore their ranking and underlying relationship. 15 CSFs were identified through a literature review, and consolidated by interviews and pilot studies with professionals in construction industry. A questionnaire instrument containing these 15 CSFs was sent out to project managers in Hong Kong, and 183 completed questionnaires were retrieved. The top three ranked factors for stakeholder management were “managing stakeholders with social responsibilities”, “assessing the stakeholders’ needs and constraints to the project”, and “communicating with stakeholders properly and frequently”. Using factor analysis and considering the high importance of the factor “managing stakeholders with social responsibilities”, the 15 CSFs were grouped into five dimensions namely, precondition factor, stakeholder estimation, information inputs, decision making, and sustainable support. All these five groupings and their relationship were included in a framework for successful stakeholder management in construction projects. These findings help to clarify what the high prioritized factors are, and could also be used as an assessment tool to evaluate the performance of stakeholder management and thus help to identify areas for improvement.SantraukaAtsižvelgiant į skirtingus suinteresuotųjų šalių valdymo aspektus, literatūroje siūlomi įvairūs kritinių sėkmės veiksnių (KSV) kompleksai. Svarbiausia yra sugrupuoti šiuos veiksnius ir nustatyti jų santykinį reikšmingumą. Šio straipsnio tikslas – nustatyti KSV, susijusius su suinteresuotųjų šalių valdymu statybos projektuose, išnagrinėti jų prioritetus ir pagrindinius tarpusavio ryšius. 15 KSV buvo nustatyta remiantis literatūros analize, statybos šakos profesionalų apklausomis ir eksperimentinėmis studijomis. Projektų valdytojams Honkonge išsiųstas klausimynas ir gauti 183 atsakymai. Trys aukščiausiai įvertinti veiksniai: projektų dalyvių socialinė atsakomybė, suinteresuotųjų šalių poreikių ir apribojimų įvertinimas, tinkamas ir dažnas bendradarbiavimas su suinteresuotomis šalimis. Naudojantis veiksnių analize ir atsižvelgiant į tai, kad socialinės atsakomybės rodiklis vertinamas kaip labai reikšmingas, 15 KSV suskirstyti į 5 grupes: išankstinių veiksnių, suinteresuotųjų grupių nustatymo, informacijos rinkimo, sprendimų priėmimo ir subalansuotos paramos. Visos šios grupės bei jų ryšiai buvo įtraukti į sistemą, skirtą sėkmingam suinteresuotųjų šalių valdymui statybos projektuose. Šie duomenys padeda paaiškinti, kokiems veiksniams suteikiamas prioritetas ir gali būti naudojami suinteresuotųjų šalių valdymo įgyvendinimui įvertinti bei tobulintinoms sritims nustatyti.First Published Online: 14 Oct 2010Reikšminiai žodžiai: kritiniai sėkmės veiksniai (KSV), suinteresuotųjų šalių valdymas, statybos projektai, rangavimas ir grupavimas, Honkongas.